Analisis Digital Forensik Keaslian Video Rekaman CCTV Menggunakan Metode Localization Tampering - Mualfah, Desti; Rizki, Yoze; Gea, Meiriladiwis (Computer Science and Information Technology, 2022)
Video is one the valid evidence if the handling process is in accordance with digital forensic procedures. Closed circuit television is a video sourse that is often used as authentic evidence in court. The authenticity of the video is something that is often doubted by certain parties. For this reason, this discusses how to detect the authenticity of video as digital evidence by comparing the original video files and tampering video files resulting from attack frame addition and attack frame delection. The media info tool is used to analyze the metadata and the localization tampering method is used to detect the frame where manipulation occurs. Localization tampering analyzes frame by frame, calculates as histogram and displays a histogram graph. Based on the results of the metadata analysis of the original video file and the video file tampering, it displays different information, which means that the video has been manipulated. Next, analyze the video with the localization tampering method to display the location on the video frame where manipulation has occurred. From the analysis results provide different information both from the calculation of the RGB value and the histogram graph.